Multicultural Interactions Decrease the Tendency to View Any Act as Unambiguously Wrong: The Moderating Role of Moral Flexibility - Liying Jiao; Ying Yang; Yan Xu (Behavioral Sciences, 2025)
In four studies, we tested whether individuals’ multicultural experiences influenced their moral judgment. Study 1 found that people’s moral judgments became more lenient after participating in short-term overseas visiting programs using a longitudinal method. Studies 2 and 3 established both correlational and experimental evidence that multicultural interactions (in-depth interactions with multiple cultures)—but not multicultural exposure (superficial exposure to multiple cultures)—predicted less harsh moral judgments. Study 4 explored the psychological mechanism and found that individuals’ moral flexibility moderated the effect of multicultural interactions on moral judgment. Specifically, multicultural interactions reduced the tendency to judge behaviors as unambiguously wrong for individuals with high moral flexibility, while for individuals with low moral flexibility, multicultural interactions did not predict moral judgments. Overall, we found that multicultural interactions readily influenced individuals’ moral judgments, and individuals’ moral character (i.e., moral flexibility) moderated this effect. These results shed light on how moral judgments are influenced by globalization.